Road Transport in Nigeria: a Study of African Enterprise - Hawkins K. E. (London: Oxford University Press, 1958)
This is a monograph, by a Research Fellow at Nuffield College, examines Nigeria's road transport industry which an is described by the author as an industry composed of firms owned and operated by Africans.
Includes index
uaa 23/01/19
Loans
Keywords: Road transport; Transportation; Nigeria